Mechanical joining methods for additive manufactured assembly tools - Pimentel, Anthony Michael Fernandes (2018)
The use of additive manufacturing (AM) processes is growing in the manufacturing industry. One application with great potential for using these processes is the manufacture of assembly tools for a high-ly competitive markets, such as the automotive industry. A critical aspect of the assembly tool design is its capability to incorporate modifications even at a late stage of its development in very short time. In many cases, these modifications are achieved using metal inserts in the polymeric tool, which allow to add new geometric features. This capability increases the usefulness and versatility of components produced by AM and compensate for potential shortcomings of using additive mate-rials. The purpose of this paper is to evaluate the potential use of accessories in additive manufactured com-ponents. In addition, the effect of different percentages of infill tool material on the joining quality of accesso-ries is evaluated. This is done by performing a screw pull-out test on a ABS ESD-7 part, produced by fused deposition modelling. The following different joining solutions were compared and studied in this work: em-bedded inserts, glue, heating processes, pressure (Tap-in) and creation of threads, such as, printing the thread directly and machining the thread onto the material.